Perancangan Instalasi LED Floodlight Berbasis Standar ICAO Annex 14 pada Main Helipad Fly Bali Heliport - Irsal Yehezkiel Paleon; I Wayan Dikse Pancane; I Wayan Sutama; I Wayan Sugara Yasa (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
Air transportation plays an important role in supporting mobility, tourism, and emergency activities such as medical evacuation and search and rescue (SAR). One of the essential supporting facilities for helicopter operations is a heliport, which must meet safety standards, including an adequate lighting system. This study aims to design an LED floodlight installation system for the Main Helipad of Fly Bali Heliport based on the international standard ICAO Annex 14 Volume II, while considering the corrosive coastal environmental conditions. The research method used is an engineering design approach with quantitative analysis of illumination requirements and current carrying capacity (CCC). Data were obtained through literature studies based on ICAO, FAA, and CAP 437 standards, as well as field observations. The design process includes determining the number and placement of floodlights, technical specifications, and electrical installation systems, including cable and protection selection. The results show that the configuration of four LED floodlight units is capable of producing a minimum illumination of 10 lux evenly across the TLOF and FATO areas in accordance with ICAO standards without causing glare. The use of Avlite AV-HL-FL floodlights with IP66 protection is suitable for coastal environments. The electrical installation system using NYY 2×2.5 mm² cables and a 2 Ampere MCB ensures system safety and reliability. Therefore, this design can enhance heliport operational safety and support optimal night operations.